INTERESTS AS PSYCHOLOGOCAL FACTOR OF SOCIAL CHANGES (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article analyses the essence of the concept of "interest". It is analysed the way new social shifts and changes provoke new organizational forms. It is illustrated that merging into new organizational forms is happening on a new basis.Most often, interest appears in scientific research as emotion, intention, concernment, desire, and activity stimulus. In Soviet psychological science, the concept of interest was identified with the concept of cognitive need. Such needs are distinguished as saturated and unsaturated. This characteristic most clearly illustrates the difference between need and interest. Interest has an unsaturated basis; it is not aimed at producing a specific result.Interest can remain the same during the life, or the realization of one interest turns to the realization of the next one. Interests can transform over time, but it is not a transformation of interest itself – it is the transformation of the Self-Concept of the individual.It is presented that interest is always conscious and rational in its essence. The emergence of interest is irrational, it always appears spontaneously.It has been researched that interest is always the result of activity. Interest opens the field of possibilities in the implementation of ideas. Social changesare different in nature. If they bring a new idea, then such an idea corresponds tothe interests, not to the needs. If social changesare dictated by unmet basic needs, then we have a social uprising (revolution).There is no social activity without interest. The space where interests prevail is the space of social change.Supporting "otherness" in social terms gives impetus to development and social shifts. The emergence of scientific and creative communities illustrates how the transition from need to interest changes the world around us.
Keywords: interest, needs (saturated, unsaturated), social changes, organizational forms, social activity.